Public value and sustainable competitive advantage of the city – the perspective of organizational theory - Wiśniewska, Magdalena (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The paper presents a new approach to management in a public organization, which is the concept of public value. The author argues that the city’s ability to achieve sustainable competitive advantage as a public organization is possible by providing city users with public value, but only involving dynamic organizational skills, and these are primarily external to the organizational boundaries of urban structures. The considerations are based on Polish and English-language literature and illustrated with empirical material concerning the largest Polish cities.